(untitled) (Research, Society and Development, 2020)
The conformation of a pedagogical strategy to science teaching is presented and discussed in this article, in the particularities of experimental sciences, entitled Problematic Experimental Activity (PEA), based on a theoretical-methodological systematization supported by theoretical articulating axes and moments methodological. Thus, the objective is to characterize a teaching stratagem that is potentially problematic in its conduct and in the reflections it originates, capable of favoring the psychological construction of scientific knowledge with an effective understanding of its circumscribed aspects, subsidized by the theory-practice relational processuality.